Synthesis of Oxindole-Appended Allyl Amines and Vinyl Aziridines via InCl3/ArSH-Mediated Ring Opening of Vinyl Aziridines and Sulfur Ylide Aziridination - Lingam, Kandapalam Arun Prasath; Shanmugam, Ponnusamy; Mandal, Asit Baran (Synlett, 2012)
A short and efficient synthesis of oxindole-appended allyl amines and 3-vinylaziridine-2-oxindoles have been accomplished in good yield via InCl3/ArSH-mediated ring opening of 3-vinylaziridine-2-oxindoles and sulfur ylide aziridination, respectively. The sulfur ylide was generated in situ from the bromo isomerized Morita–Baylis–Hillman adduct of isatin with N-tosyl imines and tetrahydrothiophene under basic conditions.
Keywords: heterocycles; oxindole; ring opening; ylides; cyclization